A new genus of Ceutorhynchinae (Coleoptera, Curculionidae). - Colonnelli, Enzo (Contributions to Entomology = Beiträge zur Entomologie, 1987)
Is described the new genus Dieckmannius, comprising the two species D. sexnotatus (Schultze, 1899) from Inida (type-species) and D. camerunensis (Hustache, 1930) from Camerun. Dieckmannius belongs to the tribe Ceutorhynchini Thomson. Nomenclatural Acts Dieckmannius Colonelli, 1987 (Curculionidae), gen. n. camerunensis (Hustache, 1930) (Dieckmannius), comb. n. hitherto Ceutorhynchus camerunensis sexnotatus (Schultze, 1899) (Dieckmannius), comb. n. hitherto Ceutorhynchus sexnotatus